Addition of Medicinal Plants Increases Antioxidant Activity, Color, and Anthocyanin Stability of Black Chokeberry (Aronia melanocarpa) Functional Beverages - Desislava Teneva; Daniela Pencheva; Ani Petrova; Manol Ognyanov; Yordan Georgiev; Petko Denev (Plants, 2022)
The present study investigates the effect of the addition of medicinal plants, such as lady’s mantle, lavender, rosehip, and meadowsweet, on the chemical composition, antioxidant activity, and color intensity of ready-to-drink aronia nectar during pasteurization and long-term storage. Pasteurization caused a significant decrease in anthocyanin content of aronia nectar, which reduced to 20% of the initial value after four months of storage. Herbs provided different protection to aronia anthocyanins that degraded more slowly during the four-month storage compared to pasteurized control without herbs. The addition of medicinal plants enriched aronia nectar with phenolic compounds and increased its antioxidant activity by up to 52% in meadowsweet-aronia nectar. Moreover, it was accompanied by a color intensity magnification due to co-pigmentation of aronia anthocyanins and herbal phenolics. In contrast to anthocyanins, which constantly degraded during the whole period, color intensity began to stabilize after 30 days, demonstrating that co-pigmentation was progressively established during the time and rosehip provided the best stabilization of aronia nectar color. Current research demonstrates for the first time that medicinal plants such as lady’s mantle, rosehip, and especially meadowsweet can be used to increase antioxidant activity, color, and anthocyanin stability of black chokeberry functional beverages.